Fabrication and Characterization of Polyimide/Aln Nanocomposite Films. Issue 2 (February 2014) - Minghua, Chen; Jinghua, Yin; Dajun, Song; Xiaoxu, Liu; Yu, Feng; Bo, Su
Polyimide/AlN (PI/AlN) nanocomposite films were prepared by in-situ polymerization method with different doping concentrations and their microstructures were investigated by small angle X-ray scattering (SAXS) technique. Analyzed SAXS results indicate the average diameters of the nanoparticles in hybrid films distribute from 55 nm to 60 nm, which are consistent with the observation from Scanning Electron Microscope (SEM). The Fourier Transform Infrared Spectroscopy (FTIR) results confirm the formation of AlN particles in the PI matrix. The effects of content on the dielectric constant, loss tangent, breakdown strength and corona ageing were studied. The corona resistant time of PI/AlN with 20 wt.% doping concentration is 58.5 hours, which is twenty times more than that of pure PI. The results show that the corona resistance of PI/AlN has been improved significantly.